Sifat Fisik Daging Sapi Dark Firm Dry (DFD) Hasil Fermentasi Bakteri Asam Laktat Lactobacillus plantarum - I I Arief; T Suryati; R.R A Maheswari (Media Peternakan, 2006)
A dark firm dry beef (DFD) can be produced in meat from animal with a degree of stress susceptibility. This type of meat is very sticky in texture and not palatable. The aim of the research was to study physical properties of DFD beef fermented by Lactobacillus plantarum combined with cold smoking. The experiment used a randomized block design. DFD beef samples were collected from beef abatoar with pH value of 6.5 - 6.8. The samples were divided into two groups; fermented by Lactobacillus plantarum and fermented naturally (control) for five days fermentation. Fermentation process was combined with cold smoking. The result showed that the pH value, tenderness and color of both groups were significantly influenced by the treatment, but the water holding capacity was not different. DFD beef fermented by Lactobacillus plantarum was more tender, lighter color and had longer sarcomere than control. Sensory analysis showed that color and tenderness of DFD beef fermented by Lactobacillus plantarum were better than control. Key words : dark firm dry beef, fermentation, Lactobacillus plantarum, color, tenderness